Low-cost photogrammetry solutions for surveying confined underground spaces: testing the traditional set-up against 360° camera on Tombs of the Kings archaeological site - D. Skarlatos; B. Cuca; G. Kafataris; M. Previtali; A. Agapiou (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This study explores low-cost photogrammetry solutions for surveying confined underground spaces, focusing on Tomb 7 at the UNESCO World Heritage Site, Tombs of the Kings in Paphos, Cyprus. The research, part of the ENGINEER project, compares traditional photogrammetric methods using frame cameras against a 360° multi-lens camera. The aim is to identify reliable, low-cost methods for 3D documentation of archaeological sites, which can be used for structural analysis and systematic monitoring. Three photogrammetric acquisition methodologies were tested: handheld with frame camera, standard with frame camera, and relaxed with 360° camera. The study evaluates the accuracy of these acquisition methods by comparing dense point clouds generated from each dataset against a reference dataset obtained via terrestrial laser scanning (TLS). Metrics such as cloud-to-cloud distance, roughness, and point cloud density were used for comparison. Results indicate that while the 360° camera offers ease of use and high data density, it also introduces more noise and variability. Traditional methods, though more time-consuming, provide more consistent and accurate results. The findings suggest that combining both approaches could optimize data quality and acquisition efficiency, making the 360° multi-lens camera a viable low-cost photogrammetry option for heritage documentation.